MOLECULAR DOCKING ANALYSIS OF HUMAN TRANSFERRIN AND LACTOFERRIN BINDING PROTEINS OF NEISSERIA MENINGITIDIS WITH 5 HYDROXY 1-4 NAPHTHOQINONE. - TRIPTI SHARMA; PIYUSH JOSHI (International Journal of Pharma and Bio Sciences, 2013)
Neisseria meningitidis is the principal cause of bacterial meningitis.. Bacteria can be transmitted by carriers through the droplets of respiratory secretions and can only infect humans. The mortality rate of bacterial meningitis is very high even after the discovery of many antibiotics. Acquisition of iron is the major determinant in the pathogenesis of Neisseria meningitidis which is fulfilled by human host proteins like transferrin, lactoferrin, hemoglobin, and haptoglobin-hemoglobin. Present study is performed on transferrin binding protein A, transferrin binding protein B, lactoferrin binding protein A and lactoferrin binding protein B which together constitutes receptors for human transferrin, and lactoferrin iron complex in Neisseria menningitidis which further are responsible for the transport of essential iron. Crystal structures of TbpA and TbpB are taken from Protein data bank while sequences of LbpA and LbpB are retrieved from NCBI and modeled by using Geno3D. Molecular docking studies are performed by taking Juglone or 5 hydroxy 1-4 naphthoqinone as a ligand. Binding energies are calculated and interactions are studied. Our findings suggest Juglone shows effective binding with these proteins with much lesser binding energies can be used for clinical trials for the treatment of meningitis.